Response to baricitinib based on prior biologic use in patients with refractory rheumatoid arthritis. (3rd February 2018) - Genovese, Mark C; Kremer, Joel M; Kartman, Cynthia E; Schlichting, Douglas E; Xie, Li; Carmack, Tara; Pantojas, Carlos; Sanchez Burson, Juan; Tony, Hans-Peter; Macias, William L; Rooney, Terence P; Smolen, Josef S
Abstract: Objective: RA patients who have failed biologic DMARDs (bDMARDs) represent an unmet medical need. We evaluated the effects of baseline characteristics, including prior bDMARD exposure, on baricitinib efficacy and safety. Methods: RA-BEACON patients (previously reported) had moderate to severe RA with insufficient response to one or more TNF inhibitor and were randomized 1:1:1 to once-daily placebo or 2 or 4 mg baricitinib. Prior bDMARD use was allowed. The primary endpoint was a 20% improvement in ACR criteria (ACR20) at week 12 for 4 mg vs placebo. An exploratory, primarily post hoc, subgroup analysis evaluated efficacy at weeks 12 and 24 by ACR20 and Clinical Disease Activity Index (CDAI) ⩽10. An interaction P -value ⩽0.10 was considered significant, with significance at both weeks 12 and 24 given more weight. Results: The odds ratios predominantly favored baricitinib over placebo and were generally similar to those in the overall study (3.4, 2.4 for ACR20 weeks 12 and 24, respectively). Significant quantitative interactions were observed for baricitinib 4 mg vs placebo at weeks 12 and 24: ACR20 by region (larger effect Europe) and CDAI ⩽10 by disease duration (larger effect ⩾10 years). No significant interactions were consistently observed for ACR20 by age; weight; disease duration; seropositivity; corticosteroid use; number of prior bDMARDs, TNF inhibitors or non-TNF inhibitors; or a specific prior TNF inhibitor. Treatment-emergent adverse event rates, including infections, appeared somewhat higher across groups with greater prior bDMARD use. Conclusion: Baricitinib demonstrated a consistent, beneficial treatment effect in bDMARD-refractory patients across subgroups based on baseline characteristics and prior bDMARD use. Trial registration: ClinicalTrials.gov (https://clinicaltrials.gov/ ), NCT01721044